Online Gender-Based Violence Study: Analysis Of Violence Against Woman - Eleanora, Fransiska Novita; Lestari, Melanie Pita; Ismail, Zulkifli (Legal Spirit, 2023)
The wider and more sophisticated the reach and development of information technology, the more popular the use of social media. However, it turns out that this technological advancement has presented a new form of violence against woman, namely online gender-based violence. This online gender-based violence can result in harm or suffering in physical, mental or sexual form, threats, coercion and the deprivation of liberty. Therefore, in this study, we will discuss Online Gender-Based Violence as a Form of Violence Against Woman. The research method used is a normative juridical research method. Based on this research, it was found that in order to prevent the occurrence of online gender-based violence, women must be aware of digital footprints, because they can be used by irresponsible parties to commit online gender-based violence and the impact can be very cruel. Woman are also less aware of the potential threats related to personal data that deviate from large impacts such as fetishization, online harassment and humiliation, threats of online violence to online trafficking of woman. Keywords : violence; gender online; woman